Emergent exchange transfusion during surgical resection of sacrococcygeal teratoma in a neonate - J.M. Davidson; T. Head; M.F. Weems; J. Jones; Y. Weatherall (Elsevier, 2022)
Sacrococcygeal teratomas (SCT) are rarely seen in neonatal period. The primary treatment is surgical resection. Stabilizing these infants preoperatively and intraoperatively has posed a challenge to pediatric specialists. The most common complications of prenatally diagnosed SCTs are high-output heart failure, tumor rupture causing hemorrhaging, and electrolyte abnormalities. Severe hyperkalemia can be lethal. We present a case where typical medical management of hyperkalemia was unsuccessful and emergent decision had to be made to perform exchange transfusion while infant was undergoing surgical resection with a good outcome.